EXPERIMENTAL AND COMPUTATIONAL STUDY OF NITROGEN-DOPED TiO2 AS A PHOTOELECTRODE - Saptari, Sitti Ahmiatri; Yuniarti, Elvan; Loua, Lamin Rene (Program Studi Fisika Universitas Negeri Jakarta, 2023)
TiO2 has been widely used as a dye-sensitized solar cell (DSSC) photoelectrode, and attempts have been made to improve the performance of the photoelectrode by adding doping. This study aims to synthesize nitrogen (N) doped TiO2 as a photoelectrode. The research was carried out experimentally and computationally using X-Ray Diffraction (XRD) test equipment, Fourier Transform Infra-Red (FTIR), and quantum espresso software using the Density Functional Theory (DFT) method. XRD results showed that TiO2 has an anatase phase, and variations in the addition of nitrogen (doped N) of 10% w/w, 20% w/w, and 30% w/w did not produce a phase change. The FTIR results of N-doped TiO2 and TiO2 provide information on the functional groups of the samples. The wave number absorption area 1626 cm-1 indicates the presence of N-H bonds with a bending vibration mode. In addition, it can be seen that there is an N-H bond with a stretching vibration mode at wave number 3436 cm-1. Computational calculations searched the band gap energy of each variation of N doping, and each obtained was 3.2 eV; 2.54 eV; 2.35 eV; and 1.64 eV. The results of this study indicate that the N-doped TiO2 photoelectrode is expected to produce better DSSC efficiency because the addition of N-doped to TiO2 causes a decrease in the bandgap energy. The N doping effect causes a new energy level. The new energy level must be positioned close to the existing valence and conduction bands. As a result, the energy required for electrons to transition from the valence band to the conduction band is reduced, effectively reducing the energy gap between the two. This change in electronic structure facilitates more effortless movement of electrons, driving increased conductivity.